Family of low dimensional materials with ternary elements Ta2NixSey: Growth strategy for Ta2NiSe5 and Ta2NiSe7 - Choi, Kyung Hwan; Jeon, Jiho; Oh, Seungbae; Chae, Sudong; Jeong, Byung Joo; Yoon, Sang Ok; Woo, Chaeheon; Dong, Xue; Ghulam, Asghar; Lim, Changmo; Seo, Minji; Kim, Tae Yeong; et al. (Journal of Alloys and Compounds, 2021)
In the ternary Ta-Ni-Se materials group, the conditions for selectively synthesizing Ta2NiSe5 and Ta2NiSe7 that exhibit a low-dimensional layered structure (due to van der Waals bonding between layers) were studied. Control of both the stoichiometric ratio of selenium and synthesis temperature facilitated the selective growth of high-quality Ta2NiSe5 and Ta2NiSe7 crystals. The synthesized low-dimensional materials could be exfoliated in a layered form, with the Ta2NiSe5 and Ta2NiSe7 layers having semiconductor and metallic electrical characteristics, respectively, as verified through the change in electrical resistance with temperature. The synthesized materials are expected to expand the repertoire of semiconducting and conducting building blocks for use in various low-dimensional devices.
Keywords: Building blockes; Electrical characteristic; Electrical resistances; Layered Structures; Low-dimensional materials; Stoichiometric ratio; Synthesis temperatures; Synthesized materials; 2D materials; Mechanical exfoliation; Powder X-ray diffraction; Quasi-1D materials; Ternary chalcogenides; van der Waals